2018
DOI: 10.7196/samj.2018.v108i5.12837
|View full text |Cite
|
Sign up to set email alerts
|

A raised serum lactate level is an independent predictor of in-hospital mortality in patients with isolated cerebral gunshot wounds

Abstract: CGSWs are associated with significant mortality, and a raised serum lactate level appears to be an independent predictor of in-hospital mortality. It is a potentially useful adjunct in the resuscitation room for identifying patients with a very poor prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Previous studies have shown the added prognostic value of lactate value in trauma patients (6,15,16). In addition, several research studies have confirmed that LAR was associated with mortality and the development of multiple organ dysfunction syndrome (MODS) in generalized or pediatric sepsis patients (11-13, 17, 18).…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies have shown the added prognostic value of lactate value in trauma patients (6,15,16). In addition, several research studies have confirmed that LAR was associated with mortality and the development of multiple organ dysfunction syndrome (MODS) in generalized or pediatric sepsis patients (11-13, 17, 18).…”
Section: Discussionmentioning
confidence: 98%
“…[ 17 ] With a lactate level of 3.3 mmol/L as the cutoff, high lactate levels at admission showed good performance in predicting in-hospital mortality in patients with cerebral gunshot injury. [ 18 ]…”
Section: Discussionmentioning
confidence: 99%
“…[17] With a lactate level of 3.3 mmol/L as the cutoff, high lactate levels at admission showed good performance in predicting in-hospital mortality in patients with cerebral gunshot injury. [18] Lee et al LAR at early phase in TBI Secondary injury after TBI, including neuroinflammation, can contribute to disruption of the blood−brain barrier (BBB). [19] Increased vascular permeability and BBB dysfunction after TBI induce leakage of albumin and fluids as well as the transmigration of immune cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Though the lactate serum 0h was above the normal level, it was not correlated with ΔGCS 24h and other outcomes, not consistent with existing research. A study of 102 gunshot patients found that serum lactate concentration was negatively correlated with the GCS scores at admission and positively correlated with in-hospital mortality 10 . A previous study of 213 moderate to severe TBI children revealed that the serum lactate concentration at admission was correlated with less mechanical ventilation time, shorter ICU LOS, hospital LOS, as well as higher mortality 11 .…”
Section: Discussionmentioning
confidence: 99%